Mortality, Cardiovascular and Limb Events in Patients With Symptomatic Lower Extremity Artery Disease and Diabetes. (July 2022) - Lapébie, François-Xavier; Bongard, Vanina; Lacroix, Philippe; Aboyans, Victor; Constans, Joël; Boulon, Carine; Messas, Emmanuel; Thomas-Delecourt, Florence; Rosenbaum, David; Ferrières, Jean; Bura-Rivière, Alessandra
The aim of this study was to compare the prognosis of patients according to diabetes status, during a 1-year follow-up after hospital admission for lower extremity artery disease, in the prospective COPART (COhorte de Patients ARTériopathes) registry. Inclusion criteria were intermittent claudication, ischemic rest pain, tissue loss, or acute limb ischemia, with radiological and hemodynamic confirmation. Among 2494 patients, 1235 (49.5%) had diabetes. Incidence rates for major adverse cardiovascular events (MACE) were 18.0/100 person-years (95% confidence interval [CI], 15.4–21.0) for the diabetes group and 11.1/100 person-years (95% CI, 9.2–13.4) for the non-diabetes group. Incidence rates of all-cause mortality were 29.8/100 person-years (95% CI, 26.5–33.4) for the diabetes group and 19.7/100 person-years (95% CI, 17.2–22.7) for the non-diabetes group. Incidence rates of major limb amputation were 24.2/100 person-years (95% CI, 21.1–27.8) for the diabetes group and 11.6/100 person-years (95% CI, 9.6–14.0) for the non-diabetes group. Diabetes was associated with MACE, adjusted hazard ratio 1.60 (95% CI, 1.16–2.22), and all-cause mortality, unadjusted HR 1.49 (95% CI, 1.24–1.78). In the multivariate analysis, diabetes was no longer associated with major amputation, adjusted HR 1.15 (95% CI, .87–1.51). Patients hospitalized for LEAD with diabetes had a higher risk of MACE than those without diabetes.